Deep Soil Mixed Wall And Jet Grouting For An Excavation Support System At The Museum Of Fine Arts In Boston, Massachusetts - Harry Schnabel (Deep Foundations Institute, 2011)
A 6200 m² cement deep soil mixed (CDSM) wall was constructed for an addition to the Museum of Fine Arts in Boston, Massachusetts. The addition was located along the east side of the existing museum within an existing courtyard and in the area of a recently demolished structure. The basement for the new addition extended up to 9.1 m below the floor slabs of the adjacent buildings. The adjacent buildings are supported on a variety of foundations including; shallow spread footings on alluvial sand deposits, low capacity piles bearing in the alluvial sands and Boston blue clay, and caissons bearing on the alluvial sands and clay. Groundwater was less than one meter below the top of the CDSM wall. The new addition was founded on shallow foundations in the desiccated crust of the Boston Blue Clay. The CDSM wall was selected as the most economical means to control deep seated ground movements, limit movements of adjacent structures, and inhibit groundwater flow into the excavation. Braces and a continuous wale were used to support the CDSM wall where it was located adjacent to structures. Tiebacks were used where there were no structures. Other geotechnical construction at the site included: ? Jet grouting (JG) to improve the ground and provide an impervious subgrade layer at the west end of the addition, ? Concrete pier underpinning was used to support an existing structure on the west end of the site, and ? A secant pile wall using alternating drilled shafts and jet grout columns was used for earth support and a barrier to groundwater flow to allow for the installation of a storage tank at the south end of the site. Inclinometers, total station surveying, vibrating wire strain gauges on the braces and wales and load cells on the tiebacks were used to monitor performance of the excavation support system. The excavation support system performed better than required limiting lateral movements of the adjacent structures to less than 13 mm and vertical settlement to less than 8 mm. No settlements or movement were detected during the construction of the wall. Lateral movement of the CDSM wall was typically below 15 mm with the maximum movement occurring near subgrade.